(untitled) (Latakia University Journal -Basic Sciences Series, 2013)
أعطت نتائج البحث الذي اعتمد على التحريات الهدروجيولوجية و التكتونية،المرتبطة بمصادر المياه العذبة في حوض السن، أن الحامل الأساس للمياه الجوفية في حوض السن يعود بشكل رئيسٍإلى الحامل المائي الجوراسي.يعتمد الحوض الصباب لنبع السن على التغذية الراشحة لمياه الأمطار و الثلوج عبر التشكيلات الجوراسية من المنطقة الشمالية والشمالية الشرقية للحوض.إن اتجاه حركة المياه الجوفية لهذا الحامل يكون نحو الغرب و الجنوب الغربي، حيث منطقة التصريف في نبع السن و الينابيع تحت البحرية قبالة الشاطئ. بينت الدراسة التكتونية وجود مجموعاتمن الشقوق و الفوالق ذات الاتجاهات NE-SW وENE-WSW و NW-SE.تتوافق حركة المياه الجوفية مع اتجاهات مجموعات الشقوق و الفوالق NE-SW و ENE-WSWو بنية فالق السن الذي يسمح بوجود علاقة تفاعلية بين الحامل المائي الرئيسي الجوراسي و بقية الحوامل الثانوية و خصوصا السينوماني. The obtained results by hydrogeological and Tectonic survey related to fresh water resources in Al-Sin Basin, indicated that the fundamental aquifer of underground water in AL-SIN region belong to Jurassic. The alimentary basin of Al-Sin spring depend upon filtration of rainfall water and snow throw Jurassic formation from north and north–east of basin. Direction of underground water circulation is toward west and south-west where we find flow place of Al-Sin spring and submarine fresh springs near seashore. Tectonical study shows the existence of fractures and fault groups with NE-SW, ENE-WSW and NW-SE directions. Groundwater movement has the same direction of fractures and faults NE-SW to ENE-WSW and Al-Sin fault structure which allow the existence of direct relation between principal Jurassic aquifer and secondary aquifer especially Cenomanian one.